(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the propositional analysis of compound sentences in the Uzbek language, focusing on their semantic and structural features. By examining the logical relationships between clauses, we aim to provide a deeper understanding of how compound sentences function within Uzbek syntax. Various linguistic theories and previous research on propositional structures are also considered to support our analysis. This study has demonstrated that compound sentences in the Uzbek language exhibit various propositional structures that reflect logical relationships between clauses. Understanding these relations is essential for both linguistic analysis and practical applications in translation and text interpretation. Future research may further explore the interaction of propositional structures with discourse and pragmatics in Uzbek.